Does Empowering Leadership and Technology Matter for Readiness for Change? The Mediating Role of Organizational Commitment in Public Organization - Estradha, Romy; Eryanto, Henry; Wibowo, Agus; Pahala, Indra; Suparno (Journal of Information and Organizational Sciences, 2025)
Organizational change is an ongoing and dynamic process that enables institutions to adapt to both internal and external developments. This study explores key factors that influence employees’ readiness to embrace change, focusing specifically on the roles of Empowering Leadership and Technology Readiness. The research examines how these factors directly and indirectly affect Readiness for Change, with Organizational Commitment acting as a mediating variable, as guided by a carefully developed conceptual and empirical model. A quantitative approach was used, employing a structured questionnaire survey distributed to change champions and change ambassadors at BPS Headquarters, Provincial Offices, and Regional Offices across Indonesia. Data from 432 valid responses were analyzed using Structural Equation Modeling (SEM) to test the proposed hypotheses and evaluate the overall model. Findings reveal that both Empowering Leadership and Technology Readiness have significant positive effects, both direct and indirect, on Readiness for Change. Organizational Commitment plays a critical mediating role in these relationships. This study contributes to theoretical literature by empirically demonstrating how leadership style and technological adaptability jointly enhances readiness in a public sector institution within a developing country. It highlights the human-centered dimensions necessary for sustaining transformation in bureaucratic settings.